Integral Values in Madrasah: to Foster Community Trust in Education - Abrori, M Sayyidul; Hadi, Moh. Solikul (Postgraduate Program Magister Pendidikan Agama Islam, 2020)
This article aims to illustrate the reality of the relationship between public trust in madrasas. The pattern of the relationship examined is not only limited to individual students, guardians of students or managers of madrasas, but to other people such as their families and society in general. This is done to understand the trust that was initially built only at the level of individual students or guardians of students or madrasah managers also occur at the level of the general public until a sociological trust is formed. In general, the community does not know and understand clearly what is a madrasa and what is a school. Madrasahs are often understood as non-formal education for madrasah diniyah which implements learning every evening.The discussion of madrasas in this paper is a formal education madrasa under the auspices of the Ministry of Religion in the field of Madrasah Education whose education level starts from the most basic level, namely RaudhatulAthfal (RA), Madrasah Ibtidaiyah (MI), Madrasah Tsanawiyah (MTs) to Madrasah Aliyah (MA) or Madrasah Aliyah Kejuruan (MAK). Where the level above is a single unit that is mutually sustainable. The results showed that the relationship of public trust is not always based on consideration of rational economic transactional but also based on moral rationality and religiosity. This is where trust develops between students or guardians of students and madrasah managers. From the perspective of symbolic interactionism, the behavior of students or guardians of students and madrasah managers reflects the meaning of worship and reinforces their relationship of trust with their religiosity.Artikel ini bertujuan untuk menggambarkan realitas hubungan antara kepercayaan publik terhadap madrasah. Pola hubungan yang diteliti tidak hanya terbatas pada siswa perorangan, wali murid atau pengelola madrasah, tetapi juga bagi orang lain seperti keluarga dan masyarakat pada umumnya. Hal ini dilakukan untuk memahami kepercayaan yang pada awalnya dibangun hanya pada tingkat siswa perorangan atau wali siswa atau manajer madrasah juga terjadi pada tingkat masyarakat umum sampai kepercayaan sosiologis terbentuk. Secara umum, masyarakat tidak tahu dan mengerti dengan jelas apa itu madrasah dan apa itu sekolah. Madrasah sering dipahami sebagai pendidikan non-formal untuk madrasah diniyah yang menerapkan pembelajaran setiap malam. Pembahasan madrasah dalam tulisan ini adalah madrasah pendidikan formal di bawah naungan Kementerian Agama di bidang Pendidikan Madrasah yang tingkat pendidikannya dimulai dari jenjang paling dasar, yaitu Raudhatul Athfal (RA), Madrasah Ibtidaiyah (MI), Madrasah Tsanawiyah (MTs) ke Madrasah Aliyah (MA) atau Madrasah Aliyah Kejuruan (MAK). Dimana level di atas adalah satu unit yang saling berkelanjutan. Hasil penelitian menunjukkan bahwa hubungan kepercayaan publik tidak selalu didasarkan pada pertimbangan transaksional ekonomi rasional tetapi juga didasarkan pada rasionalitas moral dan religiusitas. Di sinilah kepercayaan berkembang antara siswa atau wali siswa dan pengelola madrasah. Dari perspektif interaksionisme simbolik, perilaku siswa atau wali siswa dan manajer madrasah mencerminkan makna ibadah dan memperkuat hubungan kepercayaan mereka dengan agama mereka.